Factors Related To The Occurrence Of Dyspepsia At TK IV 02.07.01 Zainal Arifin Bengkulu - Yuniarsih, Tri; Wulandari, Wulandari; Darmawansyah, Darmawansyah; Suyanto, Jipri; Retni, Retni (Journal Hygeia Public Health, 2023)
Intoduction: Dyspepsia is a disorder of the upper gastrointestinal tract that often occurs with complaints of upper abdominal pain, burning sensation, nausea, vomiting, fullness, and bloating. In 2023, it was estimated that the incidence of dyspepsia increased from 10 million individuals to 28 individuals, equivalent to 11.3% of the total population in Indonesia. Dyspepsia patients rank among the top 10 diseases, with 30,154 cases (4.9%) among inpatients in hospitals in Bengkulu Province. Data from 2023 at TK IV 02.07.01 Zainul Arifin Hospital Bengkulu indicated that the number of dyspepsia patients was 223. The objective of this study is to determine the relationship between age, knowledge, and irregular eating habits with the incidence of dyspepsia at TK IV 02.07.01 Zainul Arifin Hospital, Bengkulu in 2024. Method: This research is analytical with a cross-sectional study design. The population of this study consists of all patients visiting the hospital from January to March 2024, totaling 627 individuals. The sampling technique used in this study is accidental sampling, with a sample size of 44. Result and Discussion: The results of this study show a relationship between age and the incidence of dyspepsia at the hospital in 2024 with a p-value of 0.010. There is a relationship between knowledge and the incidence of dyspepsia at the hospital in 2024 with a p-value of 0.042. There is a relationship between irregular eating habits and the incidence of dyspepsia at the hospital in 2024 with a p-value of 0.003. Conclusion: This research is expected to provide information that supports the risk factors for the incidence of dyspepsia and the need for further research on other factors that influence the differences between functional dyspepsia and organic dyspepsia based on levels of depression and anxiety.